Tri Hita Karana Leadership, Work Motivation, Work Climate, and Work Morale on Teacher Performance - Ni Made Wirawati; Basilius Redan Werang; Ni Luh Gede Erni Sulindawati (Journal of Education Action Reseach, 2026)
Teacher performance is a key factor in determining the quality of education, but various phenomena in the field suggest it is not fully optimal. This condition is related to the principal's leadership, work motivation, work climate, and teacher morale. This study aims to analyze the influence of Tri Hita Karana-based leadership, work motivation, work climate, and work morale on teacher performance in junior high schools. This study is an ex post facto, quantitative study with all teachers as the research sample. Data were collected through questionnaires and analyzed using descriptive and inferential statistics through simple and multiple linear regression. The results showed that the four variables, partially and simultaneously, had a positive and significant effect on teacher performance, with a joint contribution of 52.3%. This finding confirms that improving teacher performance can be achieved through the implementation of Tri Hita Karana-based leadership supported by high work motivation, a conducive work climate, and strong work morale. This study highlights the importance of strengthening locally rooted leadership and fostering a harmonious work environment as strategies to improve the quality of education continuously.